Pemetaan visitor and resident dalam keterlibatan individu dengan lingkungan informasi digital - Cahyaningtyas, Dwi Fitrina; Adriyana, Lasenta (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2024)
Purpose. The digital ecosystem consists of interactions between customers and partners through various channels, both online and offline, as well as the relationships that exist between digital customers and partners. The ideal interaction between humans, technology, values and activities will be created by ideal ecological information. Thus, system places consumers in an important position connecting customer contacts and contact moments with each other. Including the use of products and virtual visits, such as transactions, emails, educational media, etc. In-depth discussion of individual involvement as information organs (inforgs). Employing the activity-based mapping method, which is intended to determine each person's level of engagement with the digital environment.Methodology. The method used in this research was a pre-post test on respondents who were at Gadjah Mada University Postgraduate School postgraduate students. Questionnaires were distributed concurrently over the WhatsApp group to conduct the survey. The responses provided by respondents are entered into a Google form.Results and discussion. This study examines the use of technology and information resources by graduate students at the Graduate School of Gadjah Mada University, also known as